Studi Pengerasan Regangan (Strain Hardening) Pada Foot Step Sepeda Motor Produk Asli Dan Produk Imitasi (Lokal) - pratama, agil aditya; , Patna Partono, ST, MT (2017)
Researah material on motorcycle components can dive an idea about the quality of the physical and mechanical properties. The result will be a consideration for the nes product,ion planing ,so it is noped the new product will improving its quality this research material is focused on the strain hardening on the foot step. The purpose of the test is to check the precentage level on the elemens contained in thest form. Form this compositions (mainly carbon element) is used to looking for the austenite poin the transformation diagram and their effecton material properties. The test which been performed are microstructure,hardness and chemical position. Based on the reserch rusult,yamaha footstep original and imitasiaon product including low carbon steel material, where as the original product contain 0,178% of carbon and the imitation product contain 0,169% of carbon. The high er content of carbon (original carbon) obtaine high er rates of hardening also. The microstructure of the original and imitation productis ferrite and pearlite. The grains af ferrite and pearlite looks elongated in the outer bends.That pheno memon is due to the cold wolking that causes the grains become more dense and the shape become elongated due to its hardness prices rising, as known as strain hardening.